2021
DOI: 10.1111/jors.12551
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error in US regional economic data

Abstract: Estimates of publicly suppressed and unrevised regional economic data produce error and potentially bias statistical inference. This article estimates measurement error in suppressed cell estimated data sets (SCEDs) relative to unsuppressed federal administrative data. In a cross section, coefficient estimates based on relatively aggregated SCEDs are attenuated by about 31%, increasing to 50% in panel data. Coefficient estimates based on less-aggregated SCEDs are not generally reliable. A review of the limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…(The US Census Bureau's County Business Patterns (discussed in the Methods subsection Data) underwent greater noise infusion starting in 2017, leading to unreliable estimates of employment and establishments. See also [32]). Deller et al showed that higher initial (t − 1) values lead to slower growth as places converge to their equilibrium levels of y, p, and e.…”
Section: Conditional Growth Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…(The US Census Bureau's County Business Patterns (discussed in the Methods subsection Data) underwent greater noise infusion starting in 2017, leading to unreliable estimates of employment and establishments. See also [32]). Deller et al showed that higher initial (t − 1) values lead to slower growth as places converge to their equilibrium levels of y, p, and e.…”
Section: Conditional Growth Modelmentioning
confidence: 98%
“…Employment data came from WholeData, a data series that estimates suppressed employment values from the US Census' County Business Patterns (CBP) [37]. Carpenter et al (2021) [32] showed that WholeData has less measurement error and thereby generally reduces regression coefficient bias over common alternatives. Table 2 presents the summary statistics for nonmetropolitan counties in 2009 and data sources for the dependent and independent variables.…”
Section: Datamentioning
confidence: 99%
“…5 Given the unknown error with suppressed-cell estimated datasets (SCEDs), there is a history of efforts to improve SCEDs over the midpoint technique (Isserman & Westervelt, 2006;Orr & Buongiorno, 1989). Researchers who use SCEDs often do not document methods used to produce the estimates (Anselin et al, 1997;Gerking & Isserman, 1981;Isserman, 2001;Markusen, 1996), which may substantially bias coefficient estimates (Carpenter et al, 2021b). Additionally, researchers often resort to using relatively aggregated industries due to disclosure limitations, which can cause aggregation bias (Carpenter et al, 2021c).…”
Section: Data Summarymentioning
confidence: 99%
“…1 Following Carpenter et al (2021b), this article uses 'establishment' to refer to a physical location or 'address' where business activity takes place, and 'firm' is used to refer to a collection of establishments under a common ownership structure. 2 'Firm demography' is variously termed industrial demography, demography of the firm or enterprise, or economic demography (McCann, 2002a;van Wissen, 2005).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation